Bezbariérový rodinný dům - Kaczová, Silvia (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Predmetom projektu je novostavba bezbariérového rodinného domu v katastrálnom území Brno-Slatina. Dom je navrhnutý pre 4-člennú rodinu. Objekt nie je podsklepený a má dve nadzemné podlažia. V prvom nadzemnom podlaží sa nachádza garáž, zádverie, hlavná denná zóna, WC, technická miestnosť a pracovňa. V druhom nadzemnom podlaží sú spáľne, kúpeľňa a 2 šatne. Objekt je riešený zo murovaného systému KM Beta. Navrhnutý strop je železobetónový. Strecha je pultová so sklonom 3°. Obvodový plášť je riešený ako kontaktný zateplovací systém.

The aim of the project is a new building of a family house in the cadastral area Brno-Slatina. It is designed for a family of four. The building has no basement and two floors. On the first floor there is an entrance, garage, the main day area, WC, utility room and work room. On the second floor there are bedrooms, bathroom and 2 dressing rooms. The building is designed mainly in wall system of KM Beta. The proposed ceiling is made of ferro-concrete. The roof is pitched with angle of 3°. The facade is designed as an external thermal insulation composite system.
Barrier-free detached house
Keywords: bezbariérový rodinný dom; nepodsklepený; plochá strecha; pultová strecha; garáž; stenový systém; kontaktný zateplovací systém; barrier-free detechad house; no basement; flat roof; shed roof; garage; wall system; external thermal insulation composite system